Cardiovascular outcomes in de novo Kidney transplant recipients receiving everolimus and reduced calcineurin inhibitor or standard triple therapy: 24-month post hoc analysis from TRANSFORM study - Sommerer, Claudia; Legendre, Christophe; Citterio, Franco; Watarai, Yoshihiko; Oberbauer, Rainer; Basic-Jukic, Nikolina; Han, Jackie; Gawai, Apurva; Bernhardt, Peter; Chadban, Steve (Transplantation, 2023)
Background. - The comparative impact of everolimus (EVR)-based regimens versus standard of care (mycophenolic acid+standard calcineurin inhibitor [MPA+sCNI]) on cardiovascular outcomes in de novo kidney transplant recipients (KTRs) is poorly understood. The incidence of major adverse cardiac events (MACEs) in KTRs receiving EVR+reduced CNI (rCNI) or MPA+sCNI from the TRANSplant eFficacy and safety Outcomes with an eveRolimus-based regiMen study was evaluated. - Methods. - The incidence of MACE was determined for all randomized patients receiving at least 1 dose of the study drug. Factors associated with MACEs were determined by logistic regression. Risk of MACE out to 3 y post-study was calculated using the Patient Outcome in Renal Transplantation equation. - Results. - MACE occurred in 81 of 1014 (8.0%; EVR+rCNI) versus 89 of 1012 (8.8%; MPA+sCNI) KTRs (risk ratio, 0.91 [95% confidence interval [CI], 0.68-1.21]). The incidence of circulatory death, myocardial infarction, revascularization, or angina was similar between the arms. Incidence of MACE was similar between EVR+rCNI and MPA+sCNI arms with a higher incidence in prespecified risk groups: older age, pretransplant diabetes (15.1% versus 15.9%), statin use (8.5% versus 10.8%), and low estimated glomerular filtration rate (Month 2 estimated glomerular filtration rate <30 versus >60 mL/min/1.73 m2; odds ratio, 2.23 [95% CI, 1.02-4.86]; P = 0.044), respectively. Predicted risk of MACE within 3 y of follow-up did not differ between the treatment arms. - Conclusions. - Cardiovascular morbidity and mortality were similar between de novo KTRs receiving EVR+rCNI and MPA+sCNI. EVR+rCNI is a viable alternative to the current standard of care in KTRs. - - - - - Export